Both semantic diversity and frequency influence children’s sentence reading - Pagán, A; Bird, M; Hsiao, Y; Nation, K (Taylor and Francis, 2019)
Semantic diversity–a metric that captures variations in previous contextual experience with a word–influences children’s lexical decision and reading aloud. We investigated the effects of semantic diversity and frequency on children’s reading of words embedded in sentences, while eye movements were recorded. If semantic diversity and frequency reflect different aspects of experience that influence reading in different ways, they should show independent effects and perhaps even different processing signatures dur- ing reading. Forty-nine 9-year-olds read sentences containing high/low frequency and high/low diversity words, manipulated orthogonally. We observed main effects of both variables, with high frequency and high semantic diversity words being read more easily. These results show that variations in the amount and nature of contextual experience influence how easily words are processed during reading.